Stabilnost samospoštovanja v odnosu do narcisizma in psihološkega blagostanja - Zorjan, Saša (Psihološka obzorja (Ljubljana), 2012)
The concept of self-esteem stability has an important role in the understanding of interpersonal and psychological functioning of individuals. The purpose of this study was to examine the relationship between self-esteem stability, narcissism and psychological well-being. A total of 178 participants (77% female) participated in this study. The average age of the participants was 20, with the ages ranging from 18 to 26 years. The participants completed the following scales and questionnaires: Narcissistic Personality Inventory (NPI), Psychological Well-being Scales (PWBS), Instability of Selfesteem scale (ISES) and Rosenberg Self-esteem scale (RSES). The Rosenberg Self-esteem scale was used to measure both self-esteem level and self-esteem stability, which was defined as dispersion of self-esteem level in time. For the purpose of obtaining data on self-esteem stability, the participants were required complete the Rosenberg self-esteem scale for a sequence of 14 days, other measures were completed during the first day of participation in the study. The main effects for self-esteem level emerged for narcissism and psychological well-being, in both cases higher levels of self-esteem was associated to higher levels of narcissism and psychological well-being. Self-esteem stability additionally explained a significant proportion of variability in narcissism and psychological well-being. Self-esteem stability was negatively associated with higher levelsof narcissism and positively associated with higher levels of psychological well-being, above and beyond the effect of self-esteem level. When comparing two different measures of self-esteem stability, the results revealed that people with higher level of narcissism tend to overestimate their self-esteem stability. The results were consistent with our hypotheses. The importance of considering both level and stability of self-esteem, limitations of the present study and possibilities for further research are also discussed.
Keywords: samospoštovanje; self-esteem; narcisizem; narcissism; psihologija; psychological well-being; psychology; Rosenberg self-esteem scale (RSES); blagostanje; Instability of self-esteem scale (ISES); Lestvica samospoštovanja (RSES); Lestvica nestabilnosti samospoštovanja (ISES); Narcissistic personality inventory (NPI); Psychological well-being scales (PWBS); Vprašalnik narcisizma (NPI); Vprašalnik psihološkega blagostanja (PWBS)